Analisis Ketahanan Pangan di Kecamatan Sei Rampah Kabupaten Serdang Bedagai - TUMANGGOR, ANGGASTIAN PASI PRAYOGA; ANTARA, MADE; SUDARMA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
Analysis of Food Security in Sei Rampah Subdistrict, Serdang Bedagai District Food is the most fundamental human need with its fulfillment being the right for everyone. Fulfillment of food needs has four main aspects: food availability, food access, food utilization, food stability. In addition, nutritional status is the outcome of food security. This research aims to analyze the level of food security from three dimensions, namely, food availability, food access, and food utilization.This study uses secondary data obtained from relevant agencies, such as the Departments of Agriculture of Serdang Bedagai District and Sei Rampah. The method used in this research is calculation of indexes of food availability, food access, food utilization and the dimension of food security.The result suggests that the District of Sei Rampah is generally food secure. Looking at the dimension of food availability, 10 out of 17 villages experience high food surplus and 7 villages experience high deficit. The food access dimension of 17 villages shows high accessibility status, while the food utilization dimension shows high usefulness in every village. It is recommended that the government focuses on the proliferation of agricultural land areas in each village because so far only 10 villages produce rice and cassava. Future studies may investigate food insecurity at a broader level, such as at the level of regency and province.